2010
DOI: 10.1016/j.neuroimage.2009.12.077
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual shape sensitivity to upright and inverted faces is reflected in neuronal adaptation

Abstract: Using an fMR-adaptation paradigm for different face morphing levels we have recently demonstrated a narrow neuronal tuning to faces even at the sub-exemplar level which was tightly related to perceptual discrimination (Gilaie-Dotan and Malach, 2007). However, it is unclear whether this relationship is unique to faces or is a general property of object representations including unfamiliar objects, and whether the adaptation tuning is due to physical changes in the stimulus or to changes in perceptual discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 60 publications
10
51
0
Order By: Relevance
“…This reduction of repetition suppression effects for inverted faces is consistent with effects observed on the scalp with the same approach in normal participants (Rossion and Boremanse, 2011;Rossion et al, 2012b). More generally, inversion is a manipulation that preserves low-level features of the face but disrupts individual face discrimination performance (e.g., Yin, 1969;Freire et al, 2000;Rossion, 2008 for a review) and substantially reduces repetition suppression effects in face-selective areas (Gilaie-Dotan et al, 2010;Mazard et al, 2006;Yovel and Kanwisher, 2005). This effect is known to be highly specific to faces (i.e., non-face stimuli elicit either no inversion effect or an inversion effect of smaller magnitude than face stimuli, Yin, 1969;Rossion, 2008).…”
Section: Inverted Facessupporting
confidence: 83%
“…This reduction of repetition suppression effects for inverted faces is consistent with effects observed on the scalp with the same approach in normal participants (Rossion and Boremanse, 2011;Rossion et al, 2012b). More generally, inversion is a manipulation that preserves low-level features of the face but disrupts individual face discrimination performance (e.g., Yin, 1969;Freire et al, 2000;Rossion, 2008 for a review) and substantially reduces repetition suppression effects in face-selective areas (Gilaie-Dotan et al, 2010;Mazard et al, 2006;Yovel and Kanwisher, 2005). This effect is known to be highly specific to faces (i.e., non-face stimuli elicit either no inversion effect or an inversion effect of smaller magnitude than face stimuli, Yin, 1969;Rossion, 2008).…”
Section: Inverted Facessupporting
confidence: 83%
“…A higher response to different than same faces reflects discrimination of identity information. Studies that employed fMR-adaptation revealed higher response in the FFA to different than same upright faces but no difference between different and same inverted faces (Gilaie- Dotan et al, 2010;Mazard et al, 2006;Yovel and Kanwisher, 2005). This pattern of response is consistent with the better discrimination of upright than inverted faces -the behavioral face inversion effect.…”
Section: Face Inversion Effectsupporting
confidence: 53%
“…Several studies found no difference between the response of the FFA to upright and inverted faces or found a small effect (Aguirre et al, 1999;Epstein et al, 2006;Kanwisher et al, 1998). In later studies, the difference between the FFA's response to upright and inverted faces was larger and more consistent (Brants et al, 2011;Gilaie-Dotan et al, 2010;Mazard et al, 2006;Kanwisher, 2004, 2005). Furthermore, in studies that have used the more sensitive measure of fMR-adaptation (GrillSpector and Malach, 2001), a clear difference between the representation of identity of upright and inverted faces has emerged.…”
Section: Face Inversion Effectmentioning
confidence: 96%
“…Similarly, the N170 individual face repetition effect also disappears when faces are presented upside-down (Jacques et al, 2007). Yet, inverted faces can still be individualized well above chance level behaviorally, and smaller individual face repetition effects for inverted than upright faces have been observed in face-sensitive areas (Gilaie-Dotan et al, 2010;Goffaux et al, 2009). Moreover, in ERPs, individual face repetition effects for inverted faces are also found over right occipito-temporal leads -at a weaker magnitude -later than the N170 component (~210 ms, Jacques et al, 2007).…”
Section: The Effect Of Face Inversionmentioning
confidence: 95%